2016
DOI: 10.1017/s1368980016000446
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of parental feeding practices: does parenting style matter?

Abstract: Objectives: To combat childhood obesity, researchers have focused on parental feeding practices that promote child health. The current study investigated how parenting style relates to twelve parental feeding practices. Design: Data on parenting style and parental feeding practices were obtained for a correlational study from users of Amazon's Mechanical Turk, an online survey system. Setting: USA. Subjects: Mothers of children aged 7-11 years (n 193). Results: Parenting style related differentially to eleven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 51 publications
2
17
0
2
Order By: Relevance
“…43 Relatedly, psychological reactance theory suggests that restricting behavioural choices leads to motivation to engage in the prohibited behaviours. 44 Consistent with previous research, [25][26][27] Despite limitations, this study showed associations between parenting styles and EMA-measured child food intake and maternal feeding practices. This study furthers previous research as it is among the first to identify the role of parenting style in predicting changes in real-world parenting practices and child food intake across middle-to-late childhood.…”
Section: Maternal Feeding Behaviorssupporting
confidence: 88%
See 1 more Smart Citation
“…43 Relatedly, psychological reactance theory suggests that restricting behavioural choices leads to motivation to engage in the prohibited behaviours. 44 Consistent with previous research, [25][26][27] Despite limitations, this study showed associations between parenting styles and EMA-measured child food intake and maternal feeding practices. This study furthers previous research as it is among the first to identify the role of parenting style in predicting changes in real-world parenting practices and child food intake across middle-to-late childhood.…”
Section: Maternal Feeding Behaviorssupporting
confidence: 88%
“…Specifically, previous research reported that authoritarian parenting style was positively correlated with more use of food as a reward, pressure to eat, and less parental modeling; 14,[25][26][27] permissive parenting style was related to less monitoring of children's unhealthy food intake, 25,28 less food rules; 14 lower encouragement of consumption of healthy foods, and greater instrumental feeding; 26 and authoritative parenting style was related to increased fruit and vegetable intake, 29,30 less instrumental feeding, 26 more monitoring of healthy food intake, less pressure to eat, and more encouragement and involvement in healthy food consumption. 25,27 However, several studies have found no associations between parenting styles and child diet using more rigorous methods to assess food intake such as a 24hour dietary recall. 14,31,32 Therefore, it remains unclear if and how parenting styles differentially relate to child food intake.…”
Section: Maternal Parenting Styles Feeding Practices and Child Fomentioning
confidence: 99%
“…Parenting style in general and relation to feeding practices has also been studied in PO. Findings support the theory that authoritative parenting practices, in which parents prioritize what they believe is in their child's best interest while also accommodating some degree of child preferences, are optimal relative to authoritarian or permissive parenting styles and are associated with lower child body mass index (BMI) and increased consumption of healthier foods (Kakinami, Barnett, Seguin, & Paradis, ; Kiefner‐Burmeister, Hoffmann, Zbur, & Musher‐Eizenman, ; Langer, Seburg, JaKa, & Sherwood, ; Shloim, Edelson, Martin, & Hetherington, ; Sokol, Qin, & Poti, ). In fact, parental monitoring may have a curvilinear relationship with children's dietary behaviours whereby it is increasingly health‐promoting only up to a certain level, beyond which it becomes counterproductive (Vaughn et al, ).…”
Section: Introductionsupporting
confidence: 53%
“…General parenting style also is associated with BMI with children of authoritative parents having healthier BMIs than children whose parents have authoritarian and permissive parenting styles [ 14 ]. This difference may be because the feeding practices employed by authoritarian and permissive parents are less likely to support the development of healthy self-regulation skills in children than the feeding strategies used by authoritative parents [ 46 ]. Therefore, future nutrition interventions could benefit families by incorporating instruction on alternative methods for portion control that build children’s own self-regulation skills.…”
Section: Discussionmentioning
confidence: 99%